Assessing entrepreneurial ecosystems through a strategic value network approach: evidence from the San Francisco Area. Issue 2 (23rd February 2021) - Cavallo, Angelo; Ghezzi, Antonio; Sanasi, Silvia
Abstract : Purpose: The purpose of this article is to develop a model to assess entrepreneurial ecosystems. Specifically, the authors examine how to measure value creation and value capture mechanisms from a single participant's perspective and at the ecosystem level through a strategic value network-based approach. Design/methodology/approach: Building on extant research on strategic networks, value networks and business models and leveraging a qualitative survey, the authors develop and test an assessment tool to measure value creation and capture within the entrepreneurial ecosystem of the San Francisco Bay Area. Findings: The authors show that value-based measures on entrepreneurial ecosystems provide a systemic approach to assess how ecosystems operate, which can guide policymakers, entrepreneurs and all the other stakeholders of entrepreneurial ecosystems in their strategic decision-making process. Originality/value: The authors provide an original model grounded in the strategic management and entrepreneurship literature for entrepreneurial ecosystems' assessment as few studies have done before. Besides, the authors provide an illustrative attempt to show how to empirically apply the original model by assessing the San Francisco Bay Area's entrepreneurial ecosystem.